Evaluation of rate of pathological changes in parenchymal organs for embryo of caspian seal Phoca caspica in modern conditions of the ecosystem in the Caspian Sea - Victoria V. Volodina; Maria P. Grushko; Nadezhda N. Fedorova (Известия ТИНРО)
Pathological changes of the caspian seal fetus caused by negative processes in the mother’s organism under influence of disease and harmful environments are investigated. For that, parenchymal organs of the fetus are examined by histological methods. Active replacement of the fetus’ tissues by conjunctive tissue is detected in all organs, the most profound abnormalities are registered in the kidney and liver